Internalization of Exemplary Values in Elementary Age Children (6-12 Years) through the Code of Ethics of the Teaching Profession - Amiruddin Amiruddin; Amiruddin Siahaan; Three Wulan Ramadhani; Sitti Isni Azzaah; Rizka Amalia Rahmadhani (Universitas Pahlawan Tuanku Tambusai, 2023)
Demoralization and dehumanization are critical factors that must be considered by the teacher while speaking to the student since they are frequently linked to the teacher's sincerity in delivering the code of ethics for the discipline. The most effective internalization of educational values from teachers to students is through the exemplary method. The role model displayed by the teacher refers to the code of ethics of the teaching profession, including for elementary age children (6-12 years). This study aims to analyze the internalization of exemplary values in elementary age children through the code of ethics of the teaching profession. This type of research includes a qualitative approach with library research methods. Sources of data and materials for analysis of the study use scientific literature relevant to the topic of discussion, including books, articles, seminar proceedings, and final assignments (thesis, dissertation). The data is obtained from credible sources such as Google Scholar and Sinta. The results of this study conclude that the code of ethics is a form of regulation regarding teacher attitudes and morals in educating, teaching, and being a role model for their students, all of which have been agreed upon which have been established for all teachers in Indonesia, so that what is done by the teacher can be accounted for. and accepted by society. Furthermore, the teacher's code of ethics needs to fulfill several conditions that make the teacher said to be professional, namely a teacher must have talent and expertise, especially in understanding the character of students, and their behavior so that a teacher is said to have a healthy physical and mental health.